Morphology and morphometry of blood cells of two species of freshwater stingrays (Chondrichthyes: Potamotrygoninae) from the lower Solimões river, Amazon - MARCIO QUARA DE C. SANTOS; FLÁVIA DAYANE F. FARIAS; PAULO HENRIQUE R. ARIDE; ADRIANO T. OLIVEIRA (Anais da Academia Brasileira de Ciências)
Abstract Cytomorphological evaluation of peripheral blood provides information about the health status of animals, in addition to being indicators of environmental contamination. However, reference data regarding the size and shape of elasmobranch blood cells is limited. This work aimed to determine the morphological and morphometric of Potamotrygon motoro and Potamotrygon orbignyi blood cells. The stingrays were captured in white water environments in the lower Solimões River region, state of Amazonas, Brazil. Blood was obtained through puncture of the branchial artery using syringes with 10% EDTA. Morphological and morphometric analyses of the cells were carried out on blood samples stained with May Grunwald-Giemsa-Wright. Erythrocytes, erythroblasts (immature erythrocytes), thrombocytes, lymphocytes, monocytes, heterophils, eosinophils and basophils were identified in the blood of both species. No evidence of erythrocyte abnormalities was found, and the blood cell’s morphological characteristics were similar to those described for other species of freshwater stingrays. Despite the identical shape, the size of erythrocytes, monocytes and heterophils were significantly different between the stingray species analyzed. The information obtained in this study will assist in developing biomarkers of aquatic contamination and contribute to future research on the clinical diagnosis and conservation of freshwater stingrays.